2017
DOI: 10.1016/j.livsci.2017.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Net energy levels of reduced crude protein, amino acid-supplemented diets for heavy pigs

Abstract: This study aimed to investigate the effects of different net energy (NE) levels of diets with reduced crude protein (CP) that were supplemented with amino acids on feeding behavior, performance and carcass characteristics of heavy pigs (100-130 kg). Pigs were randomly allocated to experimental groups under a randomized complete block design with initial body weight as the blocking criterion. There were 5 treatments (NE levels: 2300, 2388, 2475, 2563 and 2650 Kcal NE/kg, as-fed basis) with 13 pigs per treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
3
1
Order By: Relevance
“…Several authors reported similar carcass weights by increasing dietary energy [7,8,27] or decreasing CP and lysine of the diet [59][60][61], although Wood et al [62] did observe that pigs fed low-CP and -AA levels had lighter carcasses than those fed high levels. Regarding carcass yield, some reports [26,27] show a linear increase as dietary energy content increased, which could be explained because low-energy diets have more fiber content, and an increase in fiber intake increases gastrointestinal tract weight, reducing carcass yield [63]. In the present study, the difference in fiber content between the control and the high-energy diet was not enough to carry out a significant increase of the gastrointestinal tract weight.…”
Section: Carcass Qualitycontrasting
confidence: 66%
See 1 more Smart Citation
“…Several authors reported similar carcass weights by increasing dietary energy [7,8,27] or decreasing CP and lysine of the diet [59][60][61], although Wood et al [62] did observe that pigs fed low-CP and -AA levels had lighter carcasses than those fed high levels. Regarding carcass yield, some reports [26,27] show a linear increase as dietary energy content increased, which could be explained because low-energy diets have more fiber content, and an increase in fiber intake increases gastrointestinal tract weight, reducing carcass yield [63]. In the present study, the difference in fiber content between the control and the high-energy diet was not enough to carry out a significant increase of the gastrointestinal tract weight.…”
Section: Carcass Qualitycontrasting
confidence: 66%
“…For the overall period in which the diets were tested (from around 80 to 137 kg BW), ADG was similar for all groups (p = 0.439). There is some unanimity in the literature [8,25,26] about the lack of effect of increasing dietary energy concentration on ADG in heavy pigs. This finding could be explained because the growth rate of pigs fed the high-energy level could be limited by the less lysine intake [27].…”
Section: Growth Performancementioning
confidence: 99%
“…Actually, Campbell & Taverner [21] employed iso-energetic feeds with various protein contents and observed no dissimilarity in ADFI. Also, other researcher reported that NE content in diets did not influence the ADFI in finishing pigs [22] and NE content with low CP did not cause influence on whole daily feed intake in growing pigs [4]. For nutrient digestibility, He et al [23] showed that 6% reduction of dietary CP indicated the highest ileal digestibility of CP and amino acid (AA).…”
Section: Growth Performance and Nutrient Digestibilitymentioning
confidence: 99%
“…2, −1.4%) of dietary NE on ADG, but a rather significant effect on NE intake. Other studies have also reported improvements in caloric efficiency when dietary NE is reduced [ 26 , 41 , 42 ]. The unexpected effect on NEE might be attributed to an additional effect of fibrous ingredients, such as wheat middlings, by limiting physical satiety [ 13 , 43 ] or to an underestimation or overestimation of the NE value of some ingredients [ 26 , 36 ].…”
Section: Discussionmentioning
confidence: 98%